BENTUK PERTUNJUKAN TARI SORENG DAN PERANNYA BAGI MASYARAKAT DESA LEMAH IRENG KECAMATAN BAWEN KABUPATEN SEMARANG - Sari, Dewi Purnama (Greget: Jurnal Kreativitas dan Studi Tari, 2023)
Soreng Dance is a traditional art form originating from Lemah Ireng Village, Bawen, Semarang Regency. This dance is an evolution of the previously established Keprajuritan Dance. Soreng Dance draws inspiration from the history of the Demak Bintara Sultanate, making it unique and special for the dancers involved. They not only perform the dance but also portray significant figures from the Demak Sultanate, creating a strong emotional connection between the dancers and the story being told. One of the distinctive features of Soreng Dance is the large number of dancers involved in the performance, reflecting the communal nature of this art form. The war theme depicted in this dance also infuses the accompaniment with energy and enthusiasm, which is highly appreciated by the audience. This makes Soreng Dance performances one of the most eagerly awaited entertainments for the community. For the people of Lemah Ireng Village, Soreng Dance is not just entertainment, but also a source of pride and a strong cultural identity. The enthusiasm shown by the villagers when watching Soreng Dance performances is proof that this art form holds deep meaning for them. The presence of Soreng Dance in the village also underscores the importance of preserving traditional arts and culture, which serves as a symbol of local pride while strengthening social bonds among the community members.